Separation Symbols in Al-Muqaddimah Ath-Thalaliyyah of Al-Mu’allaqāt by Tharafah ibn Al-ʿAbd: A Semiotic Analysis - Habib Muharrom Sudarmawan; Hanik Mahliatussikah; Alif Cahya Setiyadi; Moh. Fery Fauzi; Wildan Kamil Basyari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
This study examines the symbolic representation of separation in the first five verses of Al-Muqaddimah Ath-Thalaliyyah that opens Tharafah bin al-‘Abd al-Bakrī’s al-Mu‘allaqāt. The research aims to reveal how symbols of loss and longing are constructed through poetic imagery related to the poet’s separation from his beloved, Khaulah. The study employs a descriptive qualitative method using Michael Riffaterre’s semiotic framework, including heuristic and hermeneutic readings, as well as the identification of the matrix, model, variants, and hypogram. The heuristic reading focuses on linguistic structures, while the hermeneutic reading interprets deeper literary meanings within the poem’s cultural context. The findings show that emotional suffering caused by separation functions as the matrix governing the poem’s symbolic structure. This meaning is represented through images of abandoned ruins, fading tattoo marks, and ships crossing the waterways of Dad Valley as symbols of memory and Khaulah’s departure with her tribe. The analysis also reveals an intertextual relationship with Imru’ al-Qays’ al-Mu‘allaqāt, especially in the motif of companions consoling a grieving lover. The study also shows that symbolic expressions in the poem reflect the emotional condition of the poet and the cultural traditions of pre-Islamic Arab society. In addition, the use of semiotic analysis helps uncover implicit meanings that are not directly expressed in the text. This study contributes to Arabic literary studies by showing how Riffaterre’s semiotic theory uncovers symbolic structures and cultural meanings in classical Arabic poetry.